Muslim Home Educators in the Time of Prevent. Issue 1 (May 2020) - Pattison, Harriet
Following the implementation of the Prevent strategy in the United Kingdom and the public linking of Muslim home education with radicalization, this research explores the perspectives of Muslim home educators. Using the concept of moral panics, this paper synthesizes work on Muslim identity with that of folk devil reactions to stigmatization. Data are drawn from three case study families via questionnaires and interviews and analyzed thematically within a symbolic interactionist framework, using an adaptation of Griffiths "folk devil reaction model" as an interpretative guide. Following an exploration of participants' reflective self-appraisals, two categories of response are identified: retreat and resistance. Both of these are further subdivided, respectively, into reactions of blending in and withdrawing and reactions of drawing on resources and contestation. The paper argues that a legal and increasingly popular educational choice has been co-opted from being an individual family decision into a political narrative of danger, radicalization, and security implications. In a climate where prejudice about home education and Islam already abundantly exist, such a narrative may contribute to an increasingly intolerant society. Recognition of the situation of Muslim home educators may go some way toward tempering this.